PERLINDUNGAN HUKUM KONSUMEN TERHADAP PERJANJIAN STANDAR DALAM TRANSAKSI JUAL BELI MELALUI E-COMMERCE DI INDONESIA BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Ibrahim, Anis (STAI Darul Qalam Tangerang, 2024)
Consumer protection in transacting through internet media, how is the validity of the use of standard agreements in e-commerce buying and selling transactions in Indonesia based on the Law on Information and Electronic Transactions No. 11 of 2008, regarding this inability can be started from the fact that there is no specific definition for e-commerce within the framework of the ITE Law, because trade activities carried out electronically are understood as